Answer:
Step-by-step explanation:
Option C is the correct answer
The general equation of a circle is given by:
(x-a)^2+(x-b)^2=r^2
where:
(a,b) is the center
r is the radius
given the equation:
x^2+y^2=36
it means that the equation is centered at (0,0) with radius of 6 units. Thus a translation of 5 units to the left and 4 units up, will change the new center to
(-5,4)
thus the equation will be:
(x+5)^2+(y-4)^2=36
Answer: (x+5)^2+(y-4)^2=36
Answer:
11 pieces.Step-by-step explanation:We must divide 8 1/4 by 3/48 1/4 = 33/4Dividing:33/4 / 3/4= 33/4 * 4/3= 33/3= 11.
Step-by-step explanation:
11 pieces.Step-by-step explanation:We must divide 8 1/4 by 3/48 1/4 = 33/4Dividing:33/4 / 3/4= 33/4 * 4/3= 33/3= 11.
Step-by-step explanation:
J = 2b
M = J + 7
M = 21
J = 21 - 7
J = 14
B = 7
<em>Equation:</em>
If M is J+7, so then J = 21-7. J is 2*b, so 2*b = 21-7. Then you subtract and divide.
The number 12 would work because subtracting 2 from 12 is ten and that's basically like adding 12 to -2 :)